(untitled) (Web of Teachers: Inderscience Research, 2024)
The article presents the results of fibrogastroduodenoscopy and endoscopic hemostasis in 296 patients with ulcerative bleeding. In 292 (98.9%) patients, using various methods of hemostasis, it was possible to stop the bleeding, only in 4 (1.1%) patients it was not possible to stop the bleeding, which necessitated the need for emergency surgical intervention. Recurrent bleeding after endoscopic hemostasis developed in 8 (2.1%) patients.